Exploring clusters of defense styles, psychiatric symptoms and academic achievements among medical students: a cross-sectional study in Pakistan - Ahmed Waqas; Sadiq Naveed; Kapil Kiran Aedma; Maryam Tariq; Tayyaba Afzaal (BMC Research Notes, 2018)
Abstract Objective The clusters of participants with a homogeneous psychological make-up can be identified using sophisticated machine learning techniques such as the two-step clustering algorithm. It can also help us to identify the synergistic and additive effects of a range of psychometric variables. The identification of synergistic effect of this clustering of defense mechanism has significant practical implications as they share a certain variance. This study aims to identify the clusters of ego defenses and their relationship with academic performance and mental health outcome in medical students. Results The high achievers scored higher on mature and neurotic defense styles and lower on immature than their counter parts. A higher proportion of medical students in high achievers group had normal scores on depressive symptoms than low achievers. While a majority among low achievers suffered from severe anxiety levels than high achievers group. High achievers scored higher on sublimation, humor, anticipation, suppression, pseudo-altruism, idealization, reaction formation, autistic fantasy, denial, and rationalization.